Localisation of 11β‐Hydroxysteroid Dehydrogenase Type 2 in Mineralocorticoid Receptor Expressing Magnocellular Neurosecretory Neurones of the Rat Supraoptic and Paraventricular Nuclei. (November 2015) - Haque, M.; Wilson, R.; Sharma, K.; Mills, N. J.; Teruyama, R.
Abstract : An accumulating body of evidence suggests that the activity of the mineralocorticoid, aldosterone, in the brain via the mineralocorticoid receptor (MR) plays an important role in the regulation of blood pressure. MR was recently found in vasopressin and oxytocin synthesising magnocellular neurosecretory cells (MNCs) in both the paraventricular (PVN) and supraoptic (SON) nuclei in the hypothalamus. Considering the physiological effects of these hormones, MR in these neurones may be an important site mediating the action of aldosterone in blood pressure regulation within the brain. However, aldosterone activation of MR in the hypothalamus remains controversial as a result of the high binding affinity of glucocorticoids to MR at substantially higher concentrations compared to aldosterone. In aldosterone‐sensitive epithelia, the enzyme 11β‐hydroxysteroid dehydrogenase type 2 (11β‐HSD2) prevents glucocorticoids from binding to MR by converting glucocorticoids into inactive metabolites. The present study aimed to determine whether 11β‐HSD2, which increases aldosterone selectivity, is expressed in MNCs. Specific 11β‐HSD2 immunoreactivity was found in the cytoplasm of the MNCs in both the SON and PVN. In addition, double‐fluorescence confocal microscopy demonstrated that MR‐immunoreactivity and 11β‐HSD2‐ in situ hybridised products are colocalised in MNCs. Lastly, single‐cell reverse transcriptase‐polymerase chain reaction detected MR and 11β‐HSD2 mRNAs from cDNA libraries derived from single identified MNCs. These findings strongly suggest that MNCs in the SON and PVN are aldosterone‐sensitive neurones.